2015
DOI: 10.11113/jt.v77.3180
|View full text |Cite
|
Sign up to set email alerts
|

Selecting the Best Composting Technology Using Analytical Hierarchy Process (Ahp)

Abstract: The Analytic Hierarchy Process (AHP) has been used widely to solve multi-criteria selection problem. It is a technique that allows the decision makers to set their priorities and help make the best selection when both tangible and intangible aspects need to be considered. This study uses the AHP to select the best composting technology for the UKM composting centre where the accumulation of organic wastes are generated daily from the cafeteria and landscape activities within the UKM campus. Experts who are fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…The emphasis in social and technical aspects in the decision-making process has developed in recent years (Ghinea & Gavrilescu, 2010). Therefore, to ensure the sustainability of the decision support framework regarding composting technology for organic waste management, all four criteria (environmental, economic, social, and technical) need to be evaluated (Zurbrügg et al, 2014;Zaini et al, 2015;Bababola, 2015;Coelho et al, 2017). Table 1 shows a simplified set of criteria and sub-criteria as a basis of assessment for selecting a suitable composting technology based on previous studies.…”
Section: Assessment Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…The emphasis in social and technical aspects in the decision-making process has developed in recent years (Ghinea & Gavrilescu, 2010). Therefore, to ensure the sustainability of the decision support framework regarding composting technology for organic waste management, all four criteria (environmental, economic, social, and technical) need to be evaluated (Zurbrügg et al, 2014;Zaini et al, 2015;Bababola, 2015;Coelho et al, 2017). Table 1 shows a simplified set of criteria and sub-criteria as a basis of assessment for selecting a suitable composting technology based on previous studies.…”
Section: Assessment Criteriamentioning
confidence: 99%
“…In contrast, assessment via MCDM considers more than just two pillars of sustainability, focusing on environmental, economic, social, and technical aspects (Zaini et al, 2015;Coelho et al, 2017). Because it analyzes multiple conflicting criteria, MCDM is regarded as a complete method and the most effective decision support framework when evaluating existing or potential alternatives (Allesch & Brunner, 2014;Corelho et al, 2017).…”
Section: Assessment Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…AHP was known as an of a set of multi-attribute decision analysis methods (Hamid-Mosaku et al, 2016;Khalila et al, 2015;Umara et al, 2015;Nguyen et al, 2016b;Zaini et al, 2015). However, decision-makers regularly found that it is more convenient and more confident to use interval judgments than only a fixed value opinion (Kabir and Sumi, 2014;Paksoy et al, 2012).…”
Section: Methodsmentioning
confidence: 99%